2017
DOI: 10.1140/epjc/s10052-017-5280-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of $$f\,(R)$$ f ( R ) models on the existence of anisotropic self-gravitating systems

Abstract: This paper aims to explore some realistic configurations of anisotropic spherical structures in the background of metric f (R) gravity, where R is the Ricci scalar. The solutions obtained by Krori and Barua are used to examine the nature of particular compact stars with three different modified gravity models. The behavior of material variables is analyzed through plots and the physical viability of compact stars is investigated through energy conditions. We also discuss the behavior of different forces, equat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 109 publications
0
33
0
Order By: Relevance
“…Recently, some of the physical properties of different strange compact stars were studied in the framework of different modified gravity theories and it was concluded that all these strange stars under consideration are stable, matter content is realistic and obeys all the energy conditions [37][38][39]. In favor of modeling static objects, supposition of spherical symmetry geometry is very useful and natural while there are more options in the choice of matter content.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of the physical properties of different strange compact stars were studied in the framework of different modified gravity theories and it was concluded that all these strange stars under consideration are stable, matter content is realistic and obeys all the energy conditions [37][38][39]. In favor of modeling static objects, supposition of spherical symmetry geometry is very useful and natural while there are more options in the choice of matter content.…”
Section: Introductionmentioning
confidence: 99%
“…ese types of feasible models are f(R) � R + cR 2 [102] and f(R) � R + cR(R + αR 2 ) [42], in which one of them is recognized as quadratic curvature formulation of the generic function of Ricci scalar R and the other is the modified form of the prior model in terms of cubic corrections. Several reasonable outcomes of these models have been devoted in the literature [53,[103][104][105][106] for the physical evaluation of the collapsing star and the stable equilibrium condition of the star at the theoretical as well as the astrophysical backgrounds.…”
Section: Evolution Of Matter Density Pressure and Electric Fieldmentioning
confidence: 99%
“…e same author and his collaborators [52] determined the physical aspects of compact stellar bodies for KB line-element in modified f(R, ϕ) context. Yousaf et al [53] investigated the impacts of different viable f(R) paradigms on the existence of anisotropic stellar compact objects and found that these paradigms are well behaved at the astrophysical and the theoretical scales. e physical features of anisotropic spherically symmetric strange stars with quintessence field were discussed by Abbas et al [54] for the specific pattern of the f(R) � R + λR 2 model.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of discussion about the complexity has been assessed in various fields of science. Now in this attention several researchers have given systematic work that is shown in [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%